MONITORING POPULASI NYAMUK Aedes aegypti L. VEKTOR PENYAKIT DEMAM BERDARAH DENGUE DI KELURAHAN GEDONGKIWO KECAMATAN MANTRIJERON KOTA YOGYAKARTA - Sukesi, Tri Wahyuni (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
Background: Gedongkiwo Village is one of the villages that was ranked first for the highestnumber of dengue disease in the year 2010. Many years in the urban village health centerssupported Gedongkiwo local government has sought to control the vector mosquito Ae.aegyptiL, but such efforts until now have not shown significant results. Outreach efforts and thepromotion of public health for more attention to hygiene and environmental health are also ableto reduce the incidence of DHF has not been clearly defined. On the other hand, anotherproblem arises, namely the occurrence of resistance in mosquitoes Ae.aegypti L. of thepesticide compound that is used for eradication. The purpose of this study was to Knowing thepopulation of mosquito species Ae. Aegypti L. If visits by the House Index (HI), Container Index(CI) and Bretaeau Index (BI) in the Village District Gedongkiwo Mantrijeron Yogyakarta SpecialProvince of Yogyakarta.Methods: This was qualitative descriptive research. Samples in this study were 100 houses ineach RW 02, 06 and 09 in the Village Gedongkiwo. Data obtained by the survey to eachhousehold to determine HI, CI, and BI by filling out a check list sheet. Data analysis of theresults of research carried out in accordance with two criteria: If HI> 10% category of "high risk",HI <10% criterion "low risk"; if CI> 10% category of "high risk" and CI <10% category of "low risk"; if BI> 50% category of" high risk "and BI <50% category of" low risk ".Results: This study showed that the average value House Index (HI) in the Village Gedongkiwoof 38.67 percent and the average value of Container Index (CI) of 13.41 percent. As for theaverage value of Breateu Index (BI) is equal to 19.67 percent.Conclusion: Based on the House Index (HI) and the Container Index (CI) population ofmosquitoes Ae. aegypti L. already exceeded the safe limit the spread of dengue disease. ValueBreteau Index (BI) shows still below safe levels, but in alert condition with a variety of canincrease dengue transmission.Keyword: Monitoring, Population, Ae. aegypti L, Dengue Hemorhagic Fever, GedongkiwoVillage